LPCN 1144 Resolves NAFLD in Hypogonadal Males - Albhaisi, Somaya (Hepatol Commun, 2020)
Hypogonadism affects hepatic lipid metabolism and is expected to promote nonalcoholic fatty liver disease (NAFLD). The aims of this study were to determine (1) the prevalence of NAFLD in hypogonadal males and (2) the impact of correction of hypogonadism by LPCN 1144 (Lipocine, Inc., Salt Lake City, UT), an oral testosterone prodrug, on NAFLD in this population. Data were derived from a multicenter open‐label single‐arm trial of LPCN 1144 for hypogonadal males, in which a subset (n = 36) had serial magnetic resonance imaging–proton density fat fraction measurements (National Clinical Trial 03868059). NAFLD prevalence, defined by magnetic resonance imaging–proton density fat fraction ≥5%, was 66%. Eighty‐one percent of those with baseline liver fat (BL) ≥5% had improvement in liver fat content, and NAFLD resolved in 33% of subjects at 8 weeks (mean relative reduction: 45%) and 48% (mean relative reduction: 55%) after 16 weeks of LPCN 1144 therapy. The reduction in liver fat was greater in those with higher BL (BL ≥5%: 71%; BL ≥8%: 80%; and BL ≥10%: 75%). Normalization rate of alanine aminotransferase and gamma‐glutamyltransferase greater than the upper limit of normal range were 100% and 50% of treated patients, respectively. LPCN 1144 was not associated with major adverse events. Conclusion: Treatment with LPCN 1144 (oral T prodrug) in hypogonadal males with NAFLD resolved NAFLD in approximately half of the affected patients without any safety signals. Further studies are needed to validate its use in hypogonadal males with nonalcoholic steatohepatitis.